Tryptophan determination at carbon fiber ultramicroelectrodes by fast-scan cyclic voltammetry - Fiorucci,Antônio R. (2013)
Tryptophan determination using a fast-scan voltammetric method at carbon fiber ultramicroelectrodes (CF-UME) is described. CF-UME electrode was submitted to electrochemical pretreatment. Parameters such as number of acquisition cycles, scan rate, potential interval and electrochemical surface pretreatment were optimized. Under optimized conditions, three analytical curves were obtained for tryptophan (between 30 and 300 µmol L-1) using three different CF-UMEs pretreated by means of an optimized electrochemical treatment procedure. It was observed a dependence on the sensitivity and tryptophan concentration linear range with the radius of the electrode, with limits of detection between 16.7 and 22.7 µmol L-1. The method was applied in the determination of tryptophan in commercial samples, with errors between -0.99 and +13.2% in relation to a comparative method.